4CPS-260 Pre-anaesthesia best possible medication history for orthopaedic surgery-programmed patients. (March 2019) - Renaudin, A; Delannoy, V; Knight, M; Roux, C; Kinowski, JM; Richard, H
Abstract : Background: In the orthopaedic surgery department, anaesthetists prescribe medicines to programmed patients during the pre-surgery anaesthesia consultation. Nevertheless, a 3 month (2016) study on medication reconciliation (MR) at admission, performed by a clinical pharmacist on 215 patients, shows that despite this process, there is at least one unintended medication discrepancy (UMD) for 53% of them. A pre-anaesthesia best possible medication history (PA-BPMH) has been implemented. Purpose: This study's main objective was to test the impact of this PA-BPMH on the number of UMD. Material and methods: This was a monocentric prospective study carried out during 3 months (from February to April 2018) in an orthopaedic surgery department. Included in this study were programmed patients for three different surgeries (hip bone, knee bone and spine). The PA-BPMH was obtained before the anaesthesia consultation from data given by the patient's usual pharmacy. If necessary, the pharmacist contacted the patient. The PA-BPMH recorded into the prescription software on pre-admission was at the anaesthetists' request during the consultation. Finally, a MR was performed at admission. Results: In total, 106 patients were included, with an average age of 68 years. The PA-BPMH was possible in 83% (n=88) of them. The PA-BPMH was not obtained because of the absence of the pharmacy's contacts (7.8%; n=8) and the lack of pre-admissions (6.6%; n=7). Anaesthetists used the PA-BPMH in 89% of cases (n=78). Among patients with PA-BPMH, 76% (n=67) had a MR at admission. At least one UMD was observed in 21% (n=14) of patients at admission and this number could have been reduced to 16% if 100% of the PA-BPMH had been used. Conclusion: This test phase allowed the evaluation of the PA-BPMH's feasibility. Obtaining a BPMH before the anaesthesia consultation has reduced the number of unintended medication discrepancies at admission (53% vs 16%). The difficulty of exhaustivity led us to create a pre-anaesthesia pharmacist consultation in the patients' presence in order to improve efficiency. References and/or acknowledgements: 1. Kwan, et al. Pharmacist medication assessments in a surgical preadmission clinic. Arch Intern Med2007. 2. Van den Bemt, et al. Medication reconciliation performed by pharmacy technicians at the time of preoperative screening. Ann Pharmacother2009. No conflict of interest.